IMPLEMENTASI LISENSI WAJIB TRIPS AGREEMENT DALAM PRODUK FARMASI DI NEGARA KANADA - Melia Prabaningrum (JOURNAL EQUITABLE, 2023)
Intellectual Property Rights or also known as IPR is a translation of the term Intellectual Property Right (IPR), which means rights born based on someone's intellectual work. Trade Related Aspects of Intellectual Property Rights (hereinafter referred to as the TRIPs Agreement) as the legal basis for IPR in the international scope states. The research methodology uses normative legal research with the data used, namely laws and regulations related to the issues raised as well as some news from print and electronic media from various journals. The results of this study indicate that the country that is most effective in using mandatory licenses in the pharmaceutical sector is Canada. The Canadian Patent Act of 1923 introduced the first mandatory licensing scheme for patented foods and pharmaceutical. In the 1980s, the Government sought to increase pharmaceutical research and development in Canada by increasing protection for patented medicines. Amendments to the Patent Act of 1969 removed restrictions on local manufacturing. Anyone can obtain a compulsory license not only to manufacture but also to import any medicines produced by a patented process. One of the main reasons for the very successful compulsory licensing experience in Canada because of the simple and easy-to-use procedures.